2017
DOI: 10.1159/000484377
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Afatinib on Platelet Activation and Apoptosis

Abstract: Background/Aims: The epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor afatinib is used for the treatment of several malignancies. Afatinib is at least partially effective by triggering apoptosis of tumor cells. Platelets may similarly undergo apoptosis, which is characterized by caspase 3 activation, cell shrinkage and phosphatidylserine translocation. However, an effect of afatinib on platelets has never been reported. The present study explored whether treatment of platelets with afatinib mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…On the other hand, thrombin‐induced platelet responses were less strongly inhibited. Further investigation showed that the collagen‐induced phosphorylation of Akt was decreased by afatinib .…”
Section: Effects Of Tkis On Platelet Functionmentioning
confidence: 99%
“…On the other hand, thrombin‐induced platelet responses were less strongly inhibited. Further investigation showed that the collagen‐induced phosphorylation of Akt was decreased by afatinib .…”
Section: Effects Of Tkis On Platelet Functionmentioning
confidence: 99%
“…Individual values (mean AE SD) of female and male WT and Ga i2 -deficient mice of annexin-V-binding, platelet volume, caspase-3-positive cells, ceramide abundance, P-selectin abundance and activated integrin a IIb b3 are displayed in Table 1A-D. No significant differences were observed between male and female WT or Ga i2 -deficient mice. Phosphatidylserine exposure, a hallmark of platelet apoptosis, was quantified by flow cytometry analysis using annexin-V-binding as described previously (Cao et al 2017). As illustrated in Figure 1A and D, the percentage of PS-positive platelets in untreated resting Ga i2 À/À and WT platelets was not significantly different.…”
Section: Resultsmentioning
confidence: 81%
“…Phosphatidylserine exposure, a hallmark of platelet apoptosis, was quantified by flow cytometry analysis using annexin‐V‐binding as described previously (Cao et al. ). As illustrated in Figure A and D, the percentage of PS‐positive platelets in untreated resting Gα i2 −/− and WT platelets was not significantly different.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations